Pengaruh Peran Orang Tua dan Keaktifan Siswa Terhadap Hasil Belajar Matematika pada Masa Pandemi Covid-19 di Gugus Wonoboyo Kecamatan Wonogiri - Indriayu, Mintasih; Hariyanto, Danang; Prastiti, Tri Dyah (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2023)
This study aims to analyze the effect of: (1) the role of parents and students' activeness on mathematics learning outcomes; (2) the role of parents on student learning outcomes; and (3) students' activeness in learning mathematics. The research was carried out in the Wonoboyo Wonogiri cluster. The sample used was fifth grade students totaling 92 people. Data collection with a questionnaire. The data analysis technique uses multiple linear regression. The results of the study: (1) the variable of the role of parents with a p-value (0.000) <0.05, which means that the role of parents (X1) has a significant influence on student learning outcomes (Y). (2) Student activeness variable with p-value (0.000) <0.05, means that student activity (X2) has a significant influence on student learning outcomes (Y). (3) The results of F count (75.334) > F table (2.70) and a sig value (p-value) of 0.000 <0.05, it can be concluded that there is a joint influence between the role of parents and student activity on student learning outcomes.